"We Have a Window Seat": A Bakhtinian Analysis of International Teachers' Identity in Nazarbayev Intellectual Schools in Kazakhstan. Issue 4 (2nd October 2018) - Fimyar, Olena
Abstract : The article explores the dynamic positionality of international teachers in Nazarbayev Intellectual Schools (NIS) in Kazakhstan. The study draws on in-depth interviews with 11 international teachers from three NIS schools. The findings of the study indicate that, on the one hand, participants share a fascination with the exciting academic environment and, on the other hand, they report a degree of disaffection as a result of multiple constraints, which prevent them from being fully integrated in the life of the schools. The article contributes to the literature on teacher mobility and migration examined from the perspective of Bakhtin's dialogical approach.